2020
DOI: 10.1017/asb.2020.27
|View full text |Cite
|
Sign up to set email alerts
|

Joint Optimization of Transition Rules and the Premium Scale in a Bonus-Malus System

Abstract: Bonus-malus systems (BMSs) are widely used in actuarial sciences. These systems are applied by insurance companies to distinguish the policyholders by their risks. The most known application of BMS is in automobile third-party liability insurance. In BMS, there are several classes, and the premium of a policyholder depends on the class he/she is assigned to. The classification of policyholders over the periods of the insurance depends on the transition rules. In general, optimization of these systems involves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In this section, we give a possible application of the monotone likelihood property. In actuarial sciences, a well-studied problem to set optimal premium scale in a BM system, see Lemaire (1995), Heras et al (2004), Ágoston and Gyetvai (2020) For a small example, we assume that there are two equal-sized risk groups (A and B) in a risk community. To the risk community, the premium is set based on a common BM system.…”
Section: Applicationmentioning
confidence: 99%
“…In this section, we give a possible application of the monotone likelihood property. In actuarial sciences, a well-studied problem to set optimal premium scale in a BM system, see Lemaire (1995), Heras et al (2004), Ágoston and Gyetvai (2020) For a small example, we assume that there are two equal-sized risk groups (A and B) in a risk community. To the risk community, the premium is set based on a common BM system.…”
Section: Applicationmentioning
confidence: 99%
“…Dionne and Ghali (2005) conducted an empirical evaluation of the 1992 bonus-malus system in Tunisia. More recently, Denuit et al (2019) considered multivariate credibility modelling for usage-based motor insurance pricing with behavioural data, Vilar-Zanon et al (2020) discussed an average model approach to experience based premium rates discounts using the Spanish agricultural insurance data, and Ágoston and Gyetvai (2020) studied a joint optimisation problem of transition rules and the premium scale in a bonus-malus system. A lot more research work can be found in the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In car insurance, a posteriori information is often encoded in a bonus-malus system (BMS) which scores past claims history and directly affects the insurance prices of policy renewals by a multiplicative factor. One stream of literature on BMS studies optimal design, efficiency and economic questions related to BMS, see Loimaranta (1972), De Pril (1978, Lemaire (1995), Denuit et al (2007), Brouhns et al (2003) and Ágoston and Gyetvai (2020). A second stream of literature rather addresses the question of how an existing BMS can be used to improve the predictive power for forecasting future claims since a BMS reveals past policyholder behavior, see e.g., Boucher and Inoussa (2014), Boucher and Pigeon (2018) and Verschuren (2021).…”
Section: Introductionmentioning
confidence: 99%